Peningkatan Keterampilan Menulis melalui Strategi Pembelajaran Critical Incident pada Murid Kelas IV SDN No. 169 Inpres Parambaddo Kecamatan Polongbangkeng Utara Kabupaten Takalar - Syam, Nur (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2019)
The problem in this research is the low level of writing skills at the grade IV pupil SDN No. 169 of presidential instruction Parambaddo Sub Polongbangkeng Northern District Takalar. Formulation of the problem in this research is how improved writing skills through learning strategies Critical Incident on the disciple class IV SDN No. 169 of presidential instruction Parambaddo Sub Polongbangkeng Northern District Takalar?. The purpose of this study was to describe the improvement of writing skills through learning strategies Critical Incident on the disciple class IV SDN No. 169 of presidential instruction Parambaddo Sub Polongbangkeng Northern District Takalar. The approach used in this study is a qualitative approach. This type of research is the research action class. The focus in this research is the application of learning strategies Critical Incident and writing skills. The subject of this research is the teacher and student class IV SDN No. 169 of presidential instruction Parambaddo Sub Polongbangkeng Northern District Takalar, as many as 17 students which consists of 11 disciples male and 6 female students, who are actively enrolled in the semester odd years teaching 2018/2019. Data collection techniques used in this research is the observation, tests, and documentation. The data obtained, analyzed using qualitative descriptive analysis.  Results of research writing skills pupils on a cycle I for the average value of classes and ketuntasan of classical learning was at category enough. This suggests that the study has not yet reached the success indicators that is 65, so research proceeded to cycle II. As for the results of the research on cycle II for the average value of classes and ketuntasan of classical learning was increased to a category. This indicates that the results of the writing skills pupils have qualified from the indicators of the success of the research action class is expected, so there is no need to proceed to the next cycle.